Interactions of Reduced Deforestation and the Carbon Market: The Role of Market Regulations and Future Commitments - Niels Anger; Alistair Dixon; Erich Livengood (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Reducing emissions from deforestation and degradation (REDD) has been proposed as a potentially inexpensive and plentiful source of emission abatement to supplement other longterm climate policies. However, critics doubt that REDD credits are environmentally equivalent to domestic emission reductions, and suggest an excess supply may disrupt carbon markets. In this context, we investigate the economic implications of emissions market regulations and future emissions reduction commitments, as well as uncertainties in REDD credit supply. Numerical simulations with a multi-country equilibrium model of the global emissions market show unrestricted exchange of REDD units reduces the international carbon price by half and cuts Annex I compliance costs by roughly one third. Restricting supply or demand of REDD credits reduces price impacts, but comes at the cost of economic efficiency. Alternatively, Annex I reduction commitments could be increased by almost two thirds at constant carbon prices. While REDD provides large economic benefits for tropical rainforest regions, any REDD policy scenario also reduces wealth transfers to traditional CDM host countries through increased competition on the supply-side of the carbon market.
Keywords: Q58; D61; C60; Q23; 330; Climate Change; Kyoto Protocol; Emissions Trading; Deforestation; REDD; Klimaschutz; Emissionsrechte; Abholzung; Naturschutz; Wirtschaftspolitische Wirkungsanalyse; Emissionshandel; Simulation; Welt